(untitled) (The Voz a Vos Bulletin, 2024)
The festivities, the theater and the stage are a source of immense scenic wealth in Mexico. The so-called festivities popular have been presented since the time of the Colony and later in Mexico Independent, producing complex interactions between native cultures, European cultures, cultures Afro-descendants in addition to those come from the cultural industry of the century XIX and XX century, resulting in a dynamic cultural mix that conforms to the heritage of the so-called Popular Art. The festive theater, the street scene, the Mexican professional theater like living and moving traditions adapt, mix, and transmute into one enriched scene. When the old ritual is desacralized it tends to become theater normally inclined to the genre of the farce, whose mechanisms can be interpret and explain through theory of dramatic genres of the playwright, Mexican teacher and theorist Luisa Josefina Hernández, with her study of farce, seeking to contribute to clarifying these characteristics and operation through type or simple characters, tone holiday and replacement mechanism or symbolic to produce catharsis farsic.